Quantitative preclinical PET imaging: opportunities and challenges - Kuntner, Claudia; Stout, David B. (Frontiers in Physics, 2014)
PET imaging of metabolism involves many choices, from hardware settings, software options to animal handling considerations. How to decide what settings or conditions to use is not straightforward, as the experimental design is dependent on the particular science being investigated. There is no single answer, yet there are factors that are common to all experiments that are the subject of this review. From physics to physiology, there are many factors to consider, each of which can have a significant impact upon measurements of metabolism in vivo. This review examines the most common factors related to all types of quantitative PET imaging.